The Dynamics of the Aceh Party in the Application of Islamic Sharia - Syamsuddin Bahrum (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2019)
The Dynamics of the Aceh Party in the Application of Islamic Sharia